85 Effect of Stem Cell Infusion Therapy on Sexual Function in Men and Women with Type 2 Diabetes and Metabolic Syndrome: Results from the ACESO & CERES Clinical Trials. Issue 1 (1st April 2022) - Saltzman, R; Schulman, I; Khan, A; Hare, J; Ramasamy, R
ABSTRACT: Introduction: Despite growing interest in restorative therapies for sexual function, there exists a paucity of human research into potential therapeutic applications of stem cell therapy (SCT). Mesenchymal Stem Cells (MSCs) and its effects on sexual function have not yet been explored in patients with Type 2 Diabetes Mellitus (DM) and Metabolic Syndrome (MetS) Objective: To determine the effect of stem cell infusion therapy on sexual function in men and women with DM or MetS. Methods: We used International Index of Erectile Function (IIEF-15) collected from men and Sexual Quality of Life Questionnaire-Female (SQOL-F) collected from women enrolled in the ACESO (NCT02886884) and CERES (NCT03059355) pilot/phase I clinical trials. Participants were enrolled in the trials based on diagnosis of DM or MetS, respectively, and endothelial dysfunction - defined as Brachial Artery Flow Mediated Vasodilation (FMD) <7%. Intervention in both trials was peripheral intravenous infusion of allogeneic MSCs. Follow-up was for 1 year. Questionnaires were collected at baseline and at 1-, 3-, 6-, and 12-months post-infusion. Participants received 20 or 100 million MSCs from either bone marrow (n=21) or umbilical cord (n=6). We performed subgroup analyses evaluating dose, source, and study diseases. Descriptive and analytic statistics were used to analyze the data. Results: Data was pooled from 20 men and 7 women from the two trials. Overall, 14 received 100 million MSCs and 13 received 20 million MSCs. Median age was 61 [IQR=55-73] years. Incidence of hypertension, coronary artery disease, smoking and alcohol use were similar among each trial. Erectile dysfunction (ED) was defined by an IIEF-Erectile Function (IIEF-EF) sub-domain score ≤24 at baseline (n=16). Among men with ED, median IIEF-EF score at baseline was 5 [IQR=2-17], 6 [IQR=3-17] at 1 month, 3 [IQR=2-8] at 3 months, 4 [IQR=3-13] at 6 months, and 5.5 [IQR=2-16] at the end of 12 months (p=0.8127). Subgroup analyses revealed no changes in erectile function in either treatment dose. Similar patterns were found in other IIEF sub-domains, except median sexual desire score which increased among all men from 1-3 months post-infusion, then subsided from 6-12 months (p=0.4723). SQOL-f is a validated self-assessment questionnaire rated on a six-point scale in which higher scores reflect better female sexual quality of life. Median SQOL score among all women at baseline was 30 [IQR=19-50], 25 [IQR=23-36] at 1 month, 34 [IQR=19-46] at 3 months, 29 [IQR=21-32] at 6 months, and 34 [IQR=26-49] at the end of 12 months (p=0.8866). Main limitations of this study include the small sample size, sexual function was not a primary endpoint, and the absence of a placebo comparison arm. Conclusions: Neither ED or SQOL appears to have improved following peripheral infusion of MSCs in patients with DM and MetS, but nevertheless appears to be safe with no decline in sexual function over 1 year. The optimal route, source, and dose of SCT to enact a meaningful change in sexual function in different patient populations has yet to be determined and deserves further research in future larger randomized clinical trials. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Longeveron LLC